Learning in the Face of Adversity : The UNRWA Education Program for Palestine Refugees - Abdul-Hamid, Husein (Washington, DC, 2014)
The goal of this study is to provide a better understanding of how a school system can operate efficiently under adversity. The results of this work will be useful in identifying relevant policies in the Middle East and North Africa region. Palestine refugees are achieving higher-than-average learning outcomes in spite of the adverse circumstances they live under. Their education system the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) operates one of the largest non-governmental school systems in the Middle East. It manages nearly 700 schools, has hired 17,000 staff, educates more than 500,000 refugee students each year, and operates in five areas, including the West Bank, Gaza, Jordan, Lebanon, and Syria. This study examines three: West Bank, Gaza, and Jordan. Contrary to what might be expected from a resource-constrained administration serving refugee students who continually face a multitude of adversities, UNRWA students outperform public schools in the three regions the West Bank, Gaza, and Jordan by a year's worth of learning. This study was undertaken to better understand the reasons for success at UNRWA schools and their positive variation from comparable public schools. Econometric techniques were used to analyze international (TIMSS and Programme for International Student Assessment, or PISA) and national learning achievement data. Pedagogical practices and classroom time-on-task were observed using structured methods (Stallings model). Systems Approach for Better Education Results (SABER) tools were used to better understand the policies and implementation strategies for school and teacher management and for monitoring and evaluation. Additionally, qualitative data were collected and analyzed in line with an education resilience conceptual framework to better uncover factors that help students develop the skills to learn despite the adversities they face.